Respuesta :

Option two bc when you find the roots they change the sign

Roots of the equation  are the values of x where y = 0  

at y = 0

hence

[tex]x= 2\\x=-2\\x=-3[/tex]

are the roots of the equation  [tex]y = (x+2)(x-2) (x+3)[/tex]

so Option b  is correct

The given function is

[tex]y = (x+2)(x-2) (x+3)[/tex]........(1)

The Given graph shows the x intercepts of the functions are at

[tex]x =2 , x =-2 \; and\; x =3[/tex]

x  intercepts are also called the roots of the  equation and these  are the values of x  where y = 0  

Putting [tex]y=0[/tex] in equation (1) we get

[tex]x= 2\\x=-2\\x=-3[/tex]

For more information please refer to  the link below

https://brainly.com/question/12029673